ВСЕМИРНЫЙ ДОКЛАД О НАРКОТИКАХ 2013 год - United Nations Office on Drugs; Crime (United Nations, 2013)
The World Drug Report presents a comprehensive overview of the latest developments in drug markets. It covers production, trafficking, consumption and related health consequences. Chapter 1 of this year’s report examines the global situation and the latest trends in the different drug markets and the extent of illicit drug use, as well as the related health impact. Chapter 2 addresses the phenomenon of new psychoactive substances (NPS), which can have deadly consequences for their users but are hard to control, with dynamic, fastmutating producers and “product lines” which have emerged over the past decade.